Helping Doctoral Students Establish Long-Term Identities as Technical Communication Scholars. (April 2017) - Grant-Davie, Keith; Matheson, Breeanne; James Stephens, Eric
This article aims to help doctoral students in technical communication prepare themselves for the academic job market and for the subsequent process of earning tenure and promotion in increasingly demanding environments. The authors propose that students do four things: (a) learn to spot and articulate research problems; (b) find their vocation—the work to which they feel a personal calling—within technical communication; (c) identify the research methods that best suit their personalities; and (d) articulate a research identity and agenda that they can explain at three different levels of abstraction: describing individual projects, naming the coherent themes that connect these projects, and defining themselves concisely as scholars. All these orienting practices involve students in stepping back, looking for larger patterns in their work and in their professional interests, and finding specific language to represent them.